Upgrading Students’ Reading Skills through Digital Literacy Practices - Khumaeroh, Indri Deviriani; Mayuni, Ilza (Syntax Corporation Indonesia, 2023)
Digital literacy activities in schools, particularly in classrooms, are essential for educating students for the twenty-first century. Furthermore, digital literacy is a set of skills that allow a person to use digital devices effectively in the digital era, including easily obtaining, applying, assessing, analyzing, and synthesizing data, as well as producing new information. Furthermore, reading activities are one of the effects of this technological development. The transition from printed to digital text necessitates new literacies, such as collecting and interpreting online data. Thus, proficiency in reading is required to evaluate and interpret information from digital tools. Referring to that, this study aims to determine the extent to which digital literacy can help students improve their reading skills. A content analysis method was used in this study. This paper's data source is based on various scholarly journals. Digital platforms that are often used to improve reading skills are Facebook and Whatsapp.